PERBANDINGAN KADAR ASAM URAT PADA SERUM NON HEMOLISIS, HEMOLISIS DAN SERUM HEMOLISIS DENGAN PENAMBAHAN REAGEN ANTI-Rh - Dewi Hartati (IKesT Muhammadiyah Palembang, 2024)
Introduction: Uric acid is the final metabolic product of purines, which is a component of nucleic acids found in the nucleus of body cells. In examining uric acid, it can be seen that the normal value of uric acid levels is 2-7.5 mg/dl. Examination of uric acid levels can be affected if there is damage to the cells, causing hemolysis, hemolysis can be affected by improper sampling techniques at the pre-analytical stage. So that hemolysis can cause increased concentrations in red blood cells compared to serum or plasma thereby giving false concentrations. The addition of anti-Rh reagents to hemolytic serum aims to bind hemoglobin when the erythrocytes break down. Purpose: To determine differences in uric acid levels examined in non-hemolytic, hemolyzed and hemolyzed serum with the addition of anti-Rh reagent. Research Methods: This research is a quantitative study using a static group comparison research design. Results: the difference between uric acid levels in non-hemolytic serum samples and hemolyzed serum samples was 0.05 mg/dl or 0.87%, and hemolyzed serum samples and hemolyzed serum samples with the addition of anti-Rh reagent of 2.43 mg/dl or 37.46% whereas in non hemolyzed serum samples with hemolyzed serum samples with the addition of anti-Rh reagent of 2.38 mg/dl or 36.91%. Data analysis test using repeated ANOVA obtained p ≥ 0.000. Discussion: that there is an increase in uric acid levels in hemolyzed serum and there is a significant difference between uric acid levels in non-hemolytic serum and hemolyzed serum to hemolyzed serum with the addition of anti-Rh reagent.